THE EXTENDED STORAGE OF PORK SEMEN DILUTED WITH PANYL FRUIT WATER EGG YOLK WITH THE ADDITION OF MORINGA LEAF EXTRACT - I Kadek Agus Arsadana; Wayan Bebas; I Putu Sampurna (Buletin Veteriner Udayana, 2025)
Improving the genetic quality and population of pigs can be done through the technology of artificial insemination (AI), which requires semen storage under optimal conditions. This study aimed to evaluate the motility, viability, and abnormality of Landrace pig spermatozoa diluted using palm fruit water with the addition of 20% egg yolk and 15% Moringa leaf extract, and stored at 15°-20°C for 72 hours. This study used a completely randomized design method with four treatment groups based on the length of storage: 0 hours, 24 hours, 48 hours, and 72 hours. Fresh semen was collected from male Landrace pigs aged 1.5-2 years by massage method. Parameters measured were motility, viability, and abnormality of spermatozoa. Data were analyzed using ANOVA, followed by Games-Howell test if there were significant differences. The results showed that the length of storage had a significant effect on motility, viability, and abnormality of spermatozoa. After 72 hours of storage, sperm motility reached 40.83±1.17%, viability 53.50±1.38%, and abnormality 6.83±0.75%. The conclusion of this study is that the use of palm fruit water-based diluent with the addition of egg yolk and Moringa leaf extract still allows the storage of Landrace pig semen for 72 hours with acceptable quality. Further research is recommended to evaluate the potential of other additives to improve storability.